2012
DOI: 10.1097/dbp.0b013e3182560cd9
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Special Education Enrollment in Children With Prenatal Cocaine Exposure

Abstract: Objective This study evaluated how enrollment in special education services in 11 year old children relates to prenatal cocaine exposure, psychopathology, and other risk factors. Method Participants were 498 children enrolled in The Maternal Lifestyle Study, a prospective, longitudinal, multisite study examining outcomes of children with prenatal cocaine exposure. Logistic regression was used to examine the effect of prenatal cocaine exposure and psychopathology on enrollment in an individualized education p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…35 One study reported greater enrollment in an Individualized Education Plan (IEP) among the PCE group. 45 Oppositional defiant disorder (ODD) moderated the association, with the PCE/ODD group more likely to have an IEP than youth with only 1 condition (ODD or PCE). 45 …”
Section: Cognition/schoolmentioning
confidence: 99%
See 4 more Smart Citations
“…35 One study reported greater enrollment in an Individualized Education Plan (IEP) among the PCE group. 45 Oppositional defiant disorder (ODD) moderated the association, with the PCE/ODD group more likely to have an IEP than youth with only 1 condition (ODD or PCE). 45 …”
Section: Cognition/schoolmentioning
confidence: 99%
“…45 Oppositional defiant disorder (ODD) moderated the association, with the PCE/ODD group more likely to have an IEP than youth with only 1 condition (ODD or PCE). 45 …”
Section: Cognition/schoolmentioning
confidence: 99%
See 3 more Smart Citations